The participative democracy (Revista da Faculdade de Direito, Universidade de São Paulo, 2005)
The called "political representation", the problem of "mandate", the imperative of people representation in legislative parliaments and political parties are the main subject discussed by the emeritus professor of the University of São Paulo Law School.